Does the addition of salpingectomy or fimbriectomy to hysterectomy in premenopausal patients compromise ovarian reserve? A prospective study. (March 2017) - Naaman, Y.; Hazan, Y.; Gillor, M.; Marciano, G.; Bardenstein, R.; Shoham, Z.; Ben-Arie, A.
Abstract: Objective: To evaluate changes in ovarian reserve in patients following hysterectomy, with or without bilateral salpingectomy or fimbriectomy. Study design: Open-label, prospective cohort trial of patients undergoing hysterectomy for benign uterine indications. Levels of follicle-stimulating hormone (FSH), anti-Müllerian hormone (AMH), and ultrasonic measures of peak systolic flow velocity/diastolic velocity (S/D) ratio and resistance index (RI) in the ovarian artery were taken from patients before and 6 weeks after hysterectomy, hysterectomy + salpingectomy or hysterectomy + fimbriectomy. Results: The study period was from November 2011 to May 2014. Sixty patients were included in the final analysis, after two patients were lost to follow-up and one patient underwent bilateral oophorectomy. Of these 60 patients, 16 underwent hysterectomy alone (control group), and 44 were included in the study group (22 patients underwent hysterectomy + fimbriectomy and 22 patients underwent hysterectomy + salpingectomy). The mean age of patients was 46 years (standard deviation 4.07 years). Between-group dfferences in FSH, AMH, ovarian volume, ovarian artery S/D ratio and ovarian artery RI were not significant. Conclusion: The addition of salpingectomy or fimbriectomy to routine hysterectomy in premenopausal patients does not diminish ovarian reserve.